“Hen Wlad Fy Nhadau” (“Land of My Fathers”): A Comparative Study of Welsh Language and Culture in Settlements of Riley, Lyon, and Geary Counties, Kansas, 1850-Present - Jones, Kathyrn (Kansas State University, The Chapman Center for Rural Studies, 2012)
The author compares three types of Welsh communities found in Kansas to determine when the Welsh language ceased common usage. A variety of historic documents were used to make this determination.
Kathryn Jones, “ “Hen Wlad Fy Nhadau” (“Land of My Fathers”): A Comparative Study of Welsh Language and Culture in Settlements of Riley, Lyon, and Geary Counties, Kansas, 1850-Present,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/226.
Keywords: Riley County; Welsh Land and Emigration Society; Welsh Language; Lyon County; Eisteddfod festival; Geary County